2018
DOI: 10.1007/s11205-018-1970-8
|View full text |Cite
|
Sign up to set email alerts
|

Employment for Sustainable Development: Sectoral Efficiencies in EU Countries

Abstract: Measuring sustainable development requires multidimensional attitude as the process is characterised by compound relationships between social, economic and environmental spheres. The paper aims at assessing selected effects of sectoral employment for the three dimensions of developmental processes. We examine employment efficiency in 25 EU countries concerning four sectors: agriculture, industry, market services, and non-market services. We use a non-radial DEA input-oriented model, which allows the assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
(56 reference statements)
1
18
0
1
Order By: Relevance
“…Having controlled for relevant MSA characteristics, he finds that increases in employment variation has a significant effect on the maximum increase in unemployment rate in MSAs. However, Cyrek and Fura (2019) examined the sectorial employment for the three dimensions of developmental processes. They concluded that the structural changes in employment specified by patterns observed in the highly developed EU countries are favorable for realizing the aims of sustainable development.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Having controlled for relevant MSA characteristics, he finds that increases in employment variation has a significant effect on the maximum increase in unemployment rate in MSAs. However, Cyrek and Fura (2019) examined the sectorial employment for the three dimensions of developmental processes. They concluded that the structural changes in employment specified by patterns observed in the highly developed EU countries are favorable for realizing the aims of sustainable development.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…The inverse relationship can be explained through the following channels: (i) The poor experience much difficulty in accessing financial and credit markets, and these market imperfections can influence the occupational outcomes (Banerjee and Newman, 1993;Galor and Zeira, 1993). Besides, it hinders investment opportunities resulting in increasing inequality (Cyrek and Fura, 2019). (ii) Government spending is used on consumption services, for example, social transfer (Gozgor and Ranjan, 2017).…”
Section: Theoretical Background and Empirical Literaturementioning
confidence: 99%
“…This theory is appropriate because the strategies of strong, sustainable development characterized by economic and social dimensions (Cyrek & Fura, 2019) shaping employment structures facilitated the discovery of the level of implementation of employment services and the challenges encountered by respondents in local governments. Further, when the economy of a country fails, this will create problems and cause social instability.…”
Section: Framework Of the Studymentioning
confidence: 99%